Redukowanie luki kompetencyjnej menedżerów przez procesy organizacyjnego uczenia się - Sitko-Lutek, Agnieszka (Managers reference blank reduction through organizational learning processes, 2006)
The aim of the paper is to present the role and complexity of the managers’ competency gap definition. Managerial competencies are understood in three dimensions: knowledge, skills and attitudes. There is a need to identify and reduce the competency gap in contemporary organizations and one of the most efficient ways is to apply organizational learning processes. The author presents results of her own research concerning there sub-processes of learning: traditional, empirical, and cybernetical.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 139-146